Urinary phytoestrogen levels and reduced thyroid hormone sensitivity: a cross-sectional analysis of NHANES 2007–2010 - Zongbao Li; Fan Hu; Han Yu; Yao Yao; Yanhui Lu (European Journal of Medical Research)
Abstract Background Estrogen and thyroid hormone interact extensively in vivo, but the relationship between phytoestrogens and thyroid function and thyroid hormone sensitivity remains unclear. Methods Using 2007–2010 NHANES data of United States, we analysed the association of six urinary phytoestrogens with thyroid function and thyroid hormone sensitivity using a weighted multivariate linear regression model. Results The final analysis included 2521 euthyroid participants. After weighted multivariable adjustment (excluding dietary patterns and serum iodine levels), urinary phytoestrogen concentrations showed significant sex- and compound-specific associations with both thyroid function indicators and thyroid hormone sensitivity indices. For thyroid function, in males, Equol and Enterodiol showed negative associations with free thyroxine (FT4), while Equol, Enterodiol, and Enterolactone were negatively associated with total thyroxine (TT4). In females, Daidzein and O-Desmethylangolensin (O-DMA) demonstrated positive associations with FT4. Regarding thyroid hormone sensitivity, sex-stratified analysis revealed significant negative associations in females between Daidzein/O-DMA and FT3/FT4 ratio (P = 0.01), and between O-DMA and Thyroid Feedback Quantile-based Index (TFQI) (P = 0.04), with no significant associations observed in males. Conclusions Urinary phytoestrogens were associated with thyroid function and may adversely affect the central thyroid hormone sensitivity. Given the risk of hypothyroidism and subclinical hypothyroidism (SCH) associated with reduced thyroid hormone sensitivity, more health monitoring of people with high phytoestrogens intake is warranted.